If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13b = 27 + 4b Solving 13b = 27 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. 13b + -4b = 27 + 4b + -4b Combine like terms: 13b + -4b = 9b 9b = 27 + 4b + -4b Combine like terms: 4b + -4b = 0 9b = 27 + 0 9b = 27 Divide each side by '9'. b = 3 Simplifying b = 3
| 5y+38=124.5 | | 42x-18y+35x+47y= | | 7(-2a)=5(-3a+1) | | .4c-125=375 | | -x^2+5x=-y | | 10=-6x+16 | | 72=4x+2 | | 2x+40+x=180 | | 6(y+2)-4=6y | | 6(n-1)+4n=-86 | | 5x+12=-3x-28 | | .82=logx | | 3(3+3x)=8(x-5) | | 2.8y-7=12.85y-2 | | 2.8-7=12.85y-2 | | 59-3u=75 | | 4x+2=72 | | -5[x+3]+3=-17 | | -14v+14v=-10v | | 2y+5x-z=4y+6x | | 9x-2=9(x-7) | | 2(m-8)+7=5(m+2)-3m-19 | | 3.4=-13.6+(3.4c)+1.7 | | -[2x-8]-6=-12 | | F(-x)=3x^2+6x-5 | | x+4+2x=6x-8 | | 4(3x+4)-20=3+5x | | 4x+26=-38 | | 6w-15=9w+8 | | 11x-11=2x+16 | | 4=3(m+4) | | 4(6+x)-5=x-3 |